Mandatory Financial Reporting and Voluntary Disclosure: The Effect of Mandatory IFRS Adoption on Management Forecasts - LI, Xi (Institutional Knowledge at Singapore Management University, 2016)
This study examines the effect of the mandatory adoption of International Financial Reporting Standards (IFRS) on voluntary disclosure. Using a difference-in-difference analysis, we document a significant increase in the likelihood and frequency of management earnings forecasts following mandatory IFRS adoption, consistent with the notion that IFRS adoption alters firms' disclosure incentives in response to increased capital-market demand. We find the increase to be larger among firms domiciled in code-law countries, suggesting a catching-up effect among firms facing low disclosure incentives pre-adoption. We then propose and test three channels through which IFRS adoption could alter firms' disclosure incentives: improved earnings quality, increased shareholder demand, and increased analyst demand. We find evidence consistent with all three channels.